Cancer and Infective Endocarditis: Characteristics and Prognostic Impact - Cosyns, Bernard; Roosens, Bram; Lancellotti, Patrizio; Laroche, Cécile; Dulgheru, Raluca; Scheggi, Valentina; Vilacosta, Isidre; Pasquet, Agnès; Piper, Cornelia; Reyes, Graciela; Mahfouz, Essam; Kobalava, Zhanna; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: the interplay between cancer and IE has become of increasing interest. This study sought to assess the prevalence, baseline characteristics, management and outcomes of IE cancer patients in the ESC EORP EURO-ENDO registry. Methods: 3085 patients with IE were identified based on the ESC 2015 criteria. 359 (11.6%) IE cancer patients were compared to 2726 (88.4%) cancer-free IE patients. Results: in cancer patients, IE was mostly community-acquired (74.8%). The most frequently identified microorganisms were S. aureus (25.4%) and Enterococci (23.8%). The most frequent complications were acute renal failure (25.9%), embolic events (21.7%) and congestive heart failure (18.1%). Theoretical indication for cardiac surgery was not significantly different between groups (65.5% vs. 69.8%, P = 0.091), but was effectively less performed when indicated in IE patients with cancer (65.5% vs. 75.0%, P = 0.002). Compared to cancer-free IE patients, in-hospital and 1-year mortality occurred in 23.4% vs. 16.1%, P = 0.006, and 18.0% vs. 10.2%; P < 0.001, respectively. In IE cancer patients, predictors of mortality by multivariate analysis were creatinine > 2 mg/dL, congestive heart failure and unperformed cardiac surgery (when indicated). Conclusions: cancer in IE patients is common and associated with a worse outcome. This large, observational cohort provides new insights concerning the contemporary profile, management and clinical outcomes of IE cancer patients across a wide range of countries.